Insights from comparison of the clinical presentation and outcomes of patients hospitalized with COVID-19 in an Italian internal medicine ward during first and third wave - Ticinesi, Andrea; Parise, Alberto; Nouvenne, Antonio; Cerundolo, Nicoletta; Prati, Beatrice; Guerra, Angela; Tuttolomondo, Domenico; Gaibazzi, Nicola; Meschi, Tiziana (Frontiers in Medicine, 2023)
Background- The reasons of variability of clinical presentation of coronavirus disease-19 (COVID-19) across different pandemic waves are not fully understood, and may include individual risk profile, SARS-CoV-2 lineage and seasonal variations of viral spread. The objective of this retrospective study was to compare the characteristics and outcomes of patients admitted with confirmed coronavirus disease-19 (COVID-19) in the same season during the first (March 2020) and the third pandemic wave (March 2021, dominance of SARS-CoV-2 B.1.1.7 lineage) in an internal medicine ward of a large teaching hospital in Italy. Materials and Methods- Data of 769 unvaccinated patients (399 from the first and 370 from the third wave) were collected from clinical records, including symptom type and duration, extension of lung abnormalities on chest computed tomography (CT) and PaO2/FiO2 ratio on admission arterial blood gas analysis. Results- Third wave patients were in average younger (median 65, interquartile range [IQR] 55-75, vs 72, IQR 61-81 years old, P<0.001), with less comorbidities and better pulmonary (CT visual score median 25, IQR 15-40, vs 30, IQR 15-50, age- and sex-adjusted P=0.017) and respiratory involvement (PaO2/FiO2 median 288, IQR 237-338, vs 233, IQR 121-326 mmHg, age- and sex-adjusted P<0.001) than first wave patients. Hospital mortality was lower (19% vs 36%, P<0.001), but not for subjects over 75 years old (46% vs 49%). Age, number of chronic illnesses, PCT levels, CT visual score (Odds Ratio [OR] 1.022, 95% confidence interval [CI] 1.009-1.036, P<0.001) and PaO2/FiO2 (OR 0.991, 95% CI 0.988-0.994, P<0.001), but not the pandemic wave, were associated with mortality on stepwise multivariate logistic regression analysis. Conclusions- Despite the higher virulence of B.1.1.7 lineage, we detected milder clinical presentation and improved mortality in patients hospitalized during the third COVID-19 wave, with involvement of younger subjects. The reasons of this discrepancy are unclear, but could involve the population effect of vaccination campaigns, that were being conducted primarily in older frail subjects during the third wave.